Inkaliabum, a new Andean genus of Liabeae (Asteraceae) from Peru - Gutiérrez, Diego Germán (2010)
Inkaliabum, a new monotypic genus endemic to valleys and slopes of the Andes of Cuzco (Peru), is described. The species of genus Inkaliabum is a slender scandent subshrub with pinnately veined leaves, lacking latex, with few capitula in terminal and/or axillary capitulescences, widely campanulate involucres, many phyllaries, many florets per capitulum, and disc florets with corollas slightly differentiated into tube and throat, long style branches, and a short pubescent part of the style shaft. The new combination Inkaliabum diehlii, based on Liabum diehllii is established, and the species is illustrated. In addition, a key to the genera of Liabeae from Peru plus Oligactis is provided.